2009
DOI: 10.1029/2008jd010360
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of the atmospheric and land conditions over the Jinta oasis in northwestern China with satellite‐derived land surface parameters

Abstract: [1] Mesoscale meteorological modeling is an important tool to help understand the energy budget of the oasis, while some of its initial field data are rough limited to describe the atmosphere and land conditions over a small oasis. Local factors including land surface parameters and their interaction with the atmosphere play a dominant role in the local circulation. Therefore, in this study, land surface parameters such as land-use types, vegetation cover fraction, and surface layer soil moisture are derived b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 31 publications
3
44
0
Order By: Relevance
“…Satellite data such as land use types, vegetation fraction cover and surface-layer soil moisture were derived from the Moderate Resolution Imaging Spectroradiometer (MODIS) which gathers data in 36 spectral bands on board the Terra (EOS AM) and Aqua (EOS PM) satellites. Details of the processing and application for the satellite data can be found in the work of Meng et al (2009).…”
Section: Datasetsmentioning
confidence: 99%
See 2 more Smart Citations
“…Satellite data such as land use types, vegetation fraction cover and surface-layer soil moisture were derived from the Moderate Resolution Imaging Spectroradiometer (MODIS) which gathers data in 36 spectral bands on board the Terra (EOS AM) and Aqua (EOS PM) satellites. Details of the processing and application for the satellite data can be found in the work of Meng et al (2009).…”
Section: Datasetsmentioning
confidence: 99%
“…Once the turbulence is strong enough to break up the secondary circulation driven by the thermal heterogeneity between the oasis and the desert, water and heat exchange between the oasis and the desert will be enhanced and water vapor over the oasis will flow into the surrounding desert. It will lead to a drier oasis and may even drive the oasis into water deficiency and soil desertification (Meng et al, 2009).…”
Section: Mesoscale Circulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this area, explore the climatic effects of land use cover change (LUCC) [14,37,[40][41][42][43]. The results from the simulations using actual albedo, LAI, and VF indicated that LUCC led to local cooling of 1 • C in the summer and local warming exceeding 0.8 • C in the winter.…”
Section: Introductionmentioning
confidence: 99%
“…Gates et al, 2008a;Ma et al, 2008Ma et al, , 2009Ma et al, , 2012Huang and Wen, 2014) and atmosphericcirculation modelling studies (e.g. Gao et al, 2004;Chu et al, 2005;Meng et al, 2009Meng et al, , 2012Meng et al, , 2015Wen et al, 2012). Many of these studies involve coarse spatio-temporal resolutions.…”
Section: Introductionmentioning
confidence: 99%